The Digital Battle of God’s Attributes: Ideological Contestation in the Translation of Anthropomorphic Verses on Indonesian Quran Apps - Nadya Sa'adatur Rohmah; Wildah Nurul Islami (Journal of Digital Islamic Thought, 2026)
The digitization of the Qur'an is often considered to be the democratization of religious access, but this study argues that mobile applications have instead become an arena for ideological contestation that sharpens theological segregation. This study analyzes the politics of translating anthropomorphic verses in two of the most influential applications in Indonesia: NU Online (representing Traditional Islam) and Quran Tadabbur (representing Salafi Islam). Using Critical Discourse Analysis (CDA), this study uncovers how the developers’ ideologies are institutionalized in the text structure and application interface. The findings show a binary polarization: NU Online employs ta’wīl (metaphorical) as a means of resisting literalism, while Quran Tadabbur employs ithbāt (literal) as an instrument of doctrinal purification. Furthermore, this study finds that the technical limitations of the application trigger theological simplification, in which the richness of the interpretive tradition is reduced to a single, instant meaning. As a result, al-Qur’an applications now function as identity anchors that reinforce sectarian divisions. The digital space does not foster convergence of understanding, but rather creates fragmentation of authority, in which each theological group is locked into its own algorithmic truth.